Women's videoworks a womanual in videomaking - Dela Rosa, Alma S. (San Juan, Metro Manila Women's Action in Media, 1999)
This book serves as a guide for aspiring video makers especially for women. It contains some important points in production and direction of videos that came from the experience of the author as a camera operator, director, writer and editor of a women's television show.
Purpose: A book based on the author's "years of experience as a camera operator, director, writer, and editor of a women's television show" and a guide for an aspirant video maker especially for women, whom the author made the book for.
Contents: Working with camera. Documentation. Production. Making a video. About the author.
Keywords: Video recordings -- Production and direction -- Handbooks, manuals, etc; Video recordings -- Handbooks, manuals, etc